2000
DOI: 10.1108/13639510010355611
|View full text |Cite
|
Sign up to set email alerts
|

Predicting shooting scores from physical performance data

Abstract: Selecting the right people for police work is not only important for the employer, but is also in the best interest of the public. Failure to screen out individuals who cannot perform the physical duties has a large human and economic cost. The present study investigated whether physical performance and anthropometric measures can predict recruits' handgun marksmanship. While significant correlations were found between handgun marksmanship and dominant grip strength, combined grip strength, forearm girth and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
52
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 6 publications
(12 reference statements)
9
52
0
6
Order By: Relevance
“…Hand/arm size has been found to have a significant correlation with grip strength, with larger hands being able to exert higher forces [31]. Therefore, it could be theorized that subjects with larger upper limb measurements could shoot with more accuracy, as the gripped gun would be proportionally smaller in their hands [17]. Kayihan et al [20] also found significant correlations between wrist circumference, bicep circumference, grip strength and marksmanship.…”
Section: Fitness Measuresmentioning
confidence: 98%
See 1 more Smart Citation
“…Hand/arm size has been found to have a significant correlation with grip strength, with larger hands being able to exert higher forces [31]. Therefore, it could be theorized that subjects with larger upper limb measurements could shoot with more accuracy, as the gripped gun would be proportionally smaller in their hands [17]. Kayihan et al [20] also found significant correlations between wrist circumference, bicep circumference, grip strength and marksmanship.…”
Section: Fitness Measuresmentioning
confidence: 98%
“…During life threatening situations, a police officer may be required to aim and fire a weapon in the line of duty. Failure to perform this task accurately could result in possible harm to the officer, suspect or the general public [3,16,17]. Firing a weapon with accuracy may need to be performed under the strenuous physical demands officers may face while carrying their duty loads in unpredictable environments, as mentioned previously.…”
Section: Introductionmentioning
confidence: 99%
“…Although police work is largely sedentary (Anderson and Plecas, 2000), police officers occasionally have to deal with violence. Violence with which officers are confronted ranges from verbal threat to actual shoot-outs.…”
Section: Introductionmentioning
confidence: 99%
“…Selection and education are linked processes which bear the aim of securing competent staff, 2 since better educated police academy graduates will likely make an impact on the job performance as future police officers. 3 In other words, education is a prerequisite of efficient police work hence it has to begin with a quality candidate selection process.…”
Section: Introductionmentioning
confidence: 99%